In search of sustainable livestock management in the Dry Chaco: effect of different shrub-removal practices on vegetation - Guzman, Luis Miguel (2023)
Increasing shrub density hinders cattle raising in central Argentina rangelands. While roller- chopping and hand-cutting are used to remove shrubs and make land accessible for cattle grazing, studies on the effects of these practices on ecosystem composition, structure and functioning are scarce. We assessed the impact of shrub removal on (a) vegetation cover, composition, species richness and diversity and (b) green biomass and seasonal phenological dynamics. We used a randomised design with three treatments (degraded rangeland; roller-chopping and hand-cutting) with four replicates, and compared the treatments with the least disturbed woodland (conserved woodland). Cenchrus ciliaris L. was sown following removal treatments and grass cover increased significantly (45% roller-chopping and 84% hand-cutting vs 27% degraded rangeland, and 13% conserved woodland), and tree cover decreased (3% roller-chopping and 2% hand-cutting vs 16% degraded rangeland, and 23% conserved woodland). Shrub cover reached 45% under roller- chopping, similar to the degraded rangeland treatment (46% degraded rangeland, 60% conserved woodland), but in hand-cutting reached only 3% cover. Hand-cutting reduced species richness and vegetation diversity, whereas roller-chopping had no effect. Shrub-removal treatments decreased normalised difference vegetation index (NDVI; proxy of green biomass) and modified ecosystem phenology. Under both shrub treatments, the maximum, minimum and integral NDVI (area under the NDVI curve) were significantly lower than those of the degraded rangeland treatment. The results suggest that shrub-removal practices increase forage for livestock, but reduce functional diversity and compromise the return to less disturbed states (woodland), where tree populations are maintained.